Analisi Organizzativa e di Budget Dell'introduzione di Vedolizumab Vs Terapie Tradizionali in Colite Ulcerosa e Morbo di Crohn: Implicazioni Economiche Nel Confronto Con Adalimumab, Infliximab e Golimumab. Issue 1 (2017) - Ruggeri, Matteo; Basile, Michele; Armuzzi, Alessandro; Cicchetti, Americo
Activity-based costing and budget analysis of vedolizumab versus conventional treatments in ulcerative colitis and Crohn's disease: Objective: To assess the organizational impact of the introduction of vedolizumab compared to the biotechnological anti-TNF alternatives to date available in Italy for the management of Ulcerative Colitis (UC) and Crohn's Disease (CD). Methods: A questionnaire aimed at acquiring data about the Italian real practice concerning the management of patients affected by UC and CD was administered to a panel of expert clinicians from three Italian centers of excellence. The determination of the cost of the therapies was realized through an Activity-Based Costing (ABC) analysis which identified the differential between the use of vedolizumab and the alternatives. Results: The reduced time of infusion of vedolizumab allows a total cost/infusion of €97.89, with savings vs. infliximab of €39.60 (UC and CD). Vedolizumab implies an expenditure of €17, 229.84 (UC) and €17, 459.63 (CD) in the first year which allows, compared to Infliximab originator (€17, 739.60), a saving/patient of €509.76 and €279.97 for UC and CD respectively. In the following years, vedolizumab implies an expenditure of €13, 870.55 and €14, 049.95 for UC e CD, lower than infliximab (€14, 284.73), with a differential of €414.18 for UC and €234.78 for CD. In the comparison with infliximab biosimilar, the results are the same with regard to the administration costs, but the combined cost administration + drug is lower than that of vedolizumab due to the lower expenditure for drugs. Conclusions: Vedolizumab implies a reduction of the time spent by the professionals involved in the provision of the treatment, allowing a reallocation of the saved resources.